Irregular stone masonries: Analysis and strengthening with glass fibre reinforced composites. (1st May 2016) - Feo, L.; Luciano, R.; Misseri, G.; Rovero, L.
Abstract: Two masonry types with irregular texture are analysed to evaluate mechanical properties, sources of vulnerability and to design proper strengthening interventions. Direct surveying, laboratory and in situ tests were performed to evaluate morphological characteristics and mechanical properties. Experimental values were compared with results obtained from analytical and FEM homogenizations, which exploited automated image segmentation process to determine volume fractions and description of the Reference Volume Element. Strips of Glass Fabric-Reinforced Cementitious Matrix and transversal bars were considered and tested as strengthening solutions to overcome irregular masonries limits derived from multi-leaf structure highlighting levels of capacity improvement.